Analisis Penerapan Manajemen Risiko Berbasis ISO 31000 pada Rental Perlengkapan Outdoor: Studi Kasus Markisew Kabupaten Bandung - Dwi Julyansyah; Indy Fauziah Hanifa; Putri Dewi Renggani; Andyka Maulana Prayoga; Alfiana (Indo Publishing, 2025)
This study aims to analyze the application of the ISO 31000:2018 Risk Management framework at Markisew, an outdoor and picnic equipment rental MSME in Bandung Regency, to identify, evaluate, and formulate risk treatment strategies. The research employs a descriptive qualitative approach, where the identification of 60 risk events was classified into six main categories. Risk analysis and evaluation were conducted using a 5x5 Matrix, grouped into three priority levels: Low, Medium, and High. Evaluation results indicate that most risks fall into the Medium level (35 risks), but the main focus is directed towards six High category risks (Score 15-25), dominated by Market (R07), Operational (R36, R31), and Human Resources (R41) factors. The most crucial risks are weather dependency and extreme weather impact (R07, R36) and owner burnout risk (R41). The recommended risk treatment strategies focus on indoor product diversification for market factors, strengthening contracts and guarantees for operational and financial aspects, and recruitment and task delegation to address key man risk. This research concludes that the implementation of ISO 31000 is highly relevant for MSMEs to achieve operational stability and business sustainability.